Kontribusi Asupan Energi Protein Dan Makanan Jajanan Pada Siswa Obesitas Di Sekolah Menengah Pertama Negeri 4 Manado - Fred A. Rumagit; Phembriah S. Kereh; Juan Rori (POLTEKKES KEMENKES MANADO, 2019)
The problem of obesity and obesity in Indonesia occurs in all age groups and in all socioeconomic strata. Data Riskesdas in 2007 showed that the prevalence of obesity in Indonesia in adolescents aged 15 years and over by 19.1%, while for ages 6-14 years obesity prevalence for male gender of 9.5% and women 8.0% (Balitbangkes, 2007). The purpose of this study is to find out how the contribution of energy intake, protein intake and food snacks in obese students in SMP Negeri 4 Manado. The method in this research is observational research using Cross Sectional study design, with bivariate analysis of fisher's exact test test. Sampling technique purposive sampling. The population in this study is students of SMP Negeri 4 Manado, the sample consists of 32 male and female students in SMP Negeri 4 Manado. Measurement of dependent variable of obesity and independent variable of energy and protein intake, food snack. The results showed that 31 (96.9%) respondents had energy intake level> 90%, and 6 (18,7%) respondents had protein intake level> 90%. Most of the energy and protein intake obtained comes from food snacks. In conclusion There is a relationship between energy and protein intake derived from home-based food and snacks with obesity nutritional status.